Perbandingan Prediksi Inflasi di Indonesia Menggunakan Model Holt-Winters Exponential Smoothing Additive dan Multiplicative - Desty Rakhmawati; Muhammad Nurhalim; Septi Fajarwati (IKIP PGRI Bojonegoro, 2023)
Abstract: Inflation is an increase in the price of goods and services within a certain period of time. This inflation affects the welfare of a country. If inflation is stable and relatively low, the people's welfare will be better. Once the importance of inflation for society, so this study aims to predict inflation for the next period. Inflation data in this study were taken from BI, from January 2003 to November 2022. Based on these data, prediction analysis was carried out using the Holt-Winters Exponential Smoothing method, additive and multiplicative models. The two models are compared to determine the correct model for predicting inflation data using MAPE. MAPE results for both models obtained good category prediction values. And the more appropriate model in this study is the additive model. Keywords: Holt-Winters Exponential Smoothing, additive Model dan multiplicative Model. Abstrak:Inflasi adalah kenaikan harga barang dan jasa dalam periode waktu tertentu. Inflasi ini berpengaruh terhadap kesejahteraan di suatu Negara. Apabila inflasi stabil dan relative rendah maka kesejahteraan masyarakat semakin baik. Begitu pentingnya inflasi bagi masyarakat, sehingga penelitian ini bertujuan untuk memprediksi inflasi untuk periode kedepan. Data inflasi dalam penelitian ini diambil dari BI, dari bulan Januari 2003 sampai dengan November 2022. Berdasarkan data tersebut, maka analisis prediksi dilakukan menggunakan metode Holt-Winters Exponential Smoothing model additive dan multiplicative. Kedua model tersebut dibandingkan untuk menentukkan model yang tepat dalam prediksi data inflasi dengan menggunakan MAPE. Hasil MAPE untuk kedua model di peroleh nilai prediksi kategori baik. Dan model yang lebih tepat dalam penelitian ini adalah model additive. Kata Kunci: Holt-Winters Exponential Smoothing, Model additive dan Model multiplicative.